Small-disturbance Angle Stability Enhancement using Intelligent Redox Flow Batteries - Mohammad Taufik; Dwi Lastomo; Herlambang Setiadi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Small-disturbance angle stability or low-frequency oscillation is one of the important stability in the power system. Although damper windings and power system stabilizer (PSS) have been proved to stabilize and improve small-disturbance angle stability. However, due to increasing demand in the recent years, adding redox flow batteries (RFB) as additional devices is crucial. This paper investigates, the utilization additional devices called RFB to enhance the small-disturbance angle stability in the power system. Furthermore, ant colony optimization (ACO) method is used to tune RFB parameter. To analyze the stability improvement on the power system, single machine infinite bus is used as a test system. Eigenvalue and time domain simulation is used to examine the behavior of the investigated system. From the simulation, it is found that by installing RFB in the system, the small-disturbance angle stability of power system is improved and ACO can be a solution of tune RFB parameter.